Aortic elasticity and the influence of valve morphology in children with bicuspid aortic valve - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2018)
Aim: We investigated dimensions and elasticity of whole aorta in patients with bicuspid aortic valve and influence of valve phenotype. Method: The study group included 44 patients and 42 controls. Patients were divided into groups according to the type of valve opening as horizontal - fusion between right and left coronary cusps - and vertical - fusion between right-non-coronary cusps; according to age they were divided into younger (5-10 years) and older patients (11-16 years). Our study did not include valve phenotype with fusion between left and non-coronary cusps. Systolic-diastolic diameters of aortic annulus, sinus valsalva, sinutubular junction, arcus, and ascending-descending and abdominal aorta were measured and z-scores were obtained. Aortic strain, distensibility, and stiffness index were calculated. Flow-mediated dilatation of brachial artery was studied. Results: z-Scores at annulus, sinus valsalva, sinutubular junction, and ascending aorta were higher in study patients (p = 0.001, p = 0.0001, p = 0.0001, p = 0.0001, respectively). z-Scores of sinus valsalva and sinotubular junction were higher in the horizontal group than in the vertical group (p = 0.006, p = 0.023, respectively). z-Score was over +2 in 51% of patients with horizontal morphology and 33% of patients with vertical morphology (p = 0.0001). Ascending aorta was more distensible and less stiff in the study group (11.3 +/- 5.63 versus 7.91 +/- 4.5, p = 0.002; 4.76 +/- 3.60 versus 6.19 +/- 3.44 cm(2).dyn(-1).10(-6) p = 0.033, respectively). Stiffness index of ascending, arcus, and abdominal aorta were higher in the horizontal group (p = 0.004, p = 0.038, p = 0.006, respectively). Ascending aorta was more distensible and less stiff in the younger group (p = 0.007, p = 0.027, respectively) but did not differ in the older group compared with the control group. Conclusion: Aortic dimensions arc enlarged in patients with bicuspid aortic valve starting from childhood, suggesting the presence of generalised aortopathy. Aortic elasticity is increased at young age and decreased with age.
Keywords: Bicuspid aortic valve; children; aortic distensibility; aortic stiffness; flow mediated dilatation; 22Q11.2 DELETION SYNDROME; ASCENDING AORTA; DILATED AORTA; ROOT DILATION; ENDOTHELIAL DYSFUNCTION; CELL CHANGES; DILATATION; DISEASE; PHENOTYPE; AORTOPATHY